Governance as a Trialogue: Government-Society-Science in Transition - Turton, Anthony R.; Hattingh, Hanlie J.; Maree, Gillian A.; Roux, Dirk J.; Claassen, Marius; Strydom, Wilma F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The last two decades have been marked by a dramatic increase in global attention to the concept of governance, especially in relation to the eff- tive and sustainable management of natural resources. During this period, issues of water governance have received particular attention, for example in relation to the provision of reliable water supplies as a catalyst for p- erty eradication. Within the context of the Millennium Development Goals, and against a backdrop of an increasing frequency of water crises (ranging from widespread flooding to severe water scarcity), it is essential that each country (and particularly those countries that face development challenges) should be in a position to ensure that access to water is ava- able to those who need it most. This issue has been highlighted by the Global Water Partnership, which stated that the water crisis facing the world is in reality a crisis of governance. The South African political environment has changed dramatically in recent years, and the central concepts of social equity and the right to a healthy environment are now entrenched in the country$1 (Bs Constitution. These concepts are supported by several new laws, in particular the - tional Environmental Management Act and the National Water Act, which, in turn, are based on the principles of sustainable development. However, despite the highly desirable attributes of these landmark pieces of legis- tion, South African authorities are still struggling to implement the - quirements of these Acts almost a decade after their promulgation.s
Towards a Model for Ecosystem Governance: An Integrated Water Resource Management Example -- An Overview of Governance -- Global Experience on Governance -- National Perspectives on Water Governance: Lessons from the IWRM Planning Process in Malawi and Zambia -- Good Ecosystem Governance: Balancing Ecosystems and Social Needs -- The Role of Good Governance in Sustainable Development: Implications for Integrated Water Resource Management in Southern Africa -- Transnational Dimensions of Freshwater Ecosystem Governance -- Interrogation of the Trialogue Model -- From Dialogue to Trialogue: Sustainable Ecosystem Governance and Civil Society -- Evolution of International Norms and Values for Transboundary Groundwater Governance -- Dynamics of Transboundary Groundwater Management: Lessons from North America -- Organisational Culture as a Function of Adaptability and Responsiveness in Public Service Agencies -- Lessons from Changes in Governance of Fire Management: The Ukuvuka Operation Firestop Campaign -- The Government-and-Society Challenge in a Fledgling Democracy $1 (BEcosystem Governance in South Africa, with a Particular Focus on the Management of the Phongolo Floodplains and Reservoir -- Cross-cutting Governance Requirements -- Principles Enabling Learning Environments for Good Ecosystem Governance -- The Role of Communication in Governance: The River Health Programme as a Case Study -- An Institutional Perspective on Governance $1 (BThe Evolution of Integrated River Management in Victoria, Australia -- Conclusion -- Ecosystem Governance and the Trialogue Debate: An Overview of the Trialogue Relationship and the Engagement along Interfaces -- The Trialogue Revisited: Quo Vadis Governance?.s
Keywords: Environment; Nature; Climate change; Environmental law; Environmental policy; Environmental management; Air pollution; Environment; Atmospheric Protection/Air Quality Control/Air Pollution; Popular Science in Nature and Environment; Climate Change; Environmental Monitoring/Analysis.; Environmental Law/Policy/Ecojustice.; Environmental Management; Electronic books